2022
DOI: 10.1038/s42003-022-04401-w
|View full text |Cite
|
Sign up to set email alerts
|

Axl receptor induces efferocytosis, dampens M1 macrophage responses and promotes heart pathology in Trypanosoma cruzi infection

Abstract: Adaptive immunity controls Trypanosoma cruzi infection, but the protozoan parasite persists and causes Chagas disease. T cells undergo apoptosis, and the efferocytosis of apoptotic cells might suppress macrophages and exacerbate parasite infection. Nonetheless, the receptors involved in the efferocytosis of apoptotic lymphocytes during infection remain unknow. Macrophages phagocytose apoptotic cells by using the TAM (Tyro3, Axl, Mer) family of receptors. To address how the efferocytosis of apoptotic cells affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 67 publications
(115 reference statements)
0
13
0
Order By: Relevance
“…On the other hand, another study found a decrease in M1-associated inflammatory factor production by tumor-associated macrophages in the MDA-MB-231 xenograft breast cancer model ( 38 ). Together, these findings suggest that Axl signaling can trigger or suppress the M1 phenotype in a variety of disease settings ( 39 ). Neutrophils also play an important role in the early stages of respiratory disorders, including silicosis ( 40 ).…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, another study found a decrease in M1-associated inflammatory factor production by tumor-associated macrophages in the MDA-MB-231 xenograft breast cancer model ( 38 ). Together, these findings suggest that Axl signaling can trigger or suppress the M1 phenotype in a variety of disease settings ( 39 ). Neutrophils also play an important role in the early stages of respiratory disorders, including silicosis ( 40 ).…”
Section: Discussionmentioning
confidence: 94%
“…To address the role of efferocytosis during T. cruzi infection, we employed two mouse strains individually defective in Axl and Mer, two out of three TAM receptors involved in efferocytosis ( 14 ). Double Mer -/- Axl -/- and single Mer-defective strains have been previously used in Leishmania infection to show that infected neutrophils transfer Leishmania parasites to macrophages or DCs through efferocytosis and reduce macrophage and T cell responses ( 77 , 78 ).…”
Section: Efferocytosis Suppresses Macrophage-mediated Immunitymentioning
confidence: 99%
“…By employing bone marrow-derived macrophages treated with a TAM receptor inhibitor or Mer- and Axl-defective macrophages, we investigated macrophage responses to T cells from T. cruzi -infected mice, which bear both effector activity and proapoptotic cells ( 14 ). Efferocytosis of apoptotic T cells was blocked by a TAM receptor inhibitor, whereas Mer or Axl deficiency partially inhibited efferocytosis ( 14 ). Remarkably, TAM inhibition and Axl but not Mer deficiency improved M1 responses to T cells from T. cruzi -infected mice ( 14 ).…”
Section: Efferocytosis Suppresses Macrophage-mediated Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…The role of AXL is controversial with studies showing that induction of M1 macrophage phenotype, but also M2 macrophage signature, can be induced by AXL depending on the cytokine environment and disease context. Additionally, AXL contributes to efferocytosis in the context of inflammatory environments [ 63 , 64 , 65 , 66 ]. In contrast, MERTK is strongly connected to M2 macrophage polarization status and is essential for efferocytosis predominantly in anti-inflammatory environments [ 67 , 68 , 69 , 70 ].…”
Section: Role Of Tam Receptors In Bone Remodelingmentioning
confidence: 99%